Indigenous–non-Indigenous disparities in health and social outcomes 5 years after first episode psychosis: national cohort study - Ruth Cunningham; Frederieke Petrović-van der Deen; Sheree Gibb; Marie Crowe; Jenni Manuel; Suzanne Pitama; Sue Crengle; Richard Porter; Cameron Lacey (BJPsych Open)
Background There are ethnic differences, including differences related to indigeneity, in the incidence of first episode psychosis (FEP) and pathways into care, but research on ethnic disparities in outcomes following FEP is limited.